WYMOGI WSPÓŁCZESNEGO RYNKU PRACY W ODNIESIENIU DO KOMPETENCJI ABSOLWENTÓW KIERUNKÓW HUMANISTYCZNYCH - Dańko, Magdalena; Wieszczeczyńska, Ewa (Neofilolog, 2019)
This paper presents the results of a pilot study conducted in 60 selected companies located in Wrocław and Lower Silesia. The main objective of the study was to get information about prospective employers’ expectations of graduates of humanities with foreign language knowledge and skills, should those companies decide to employ them. It was found that according to employers social and personal competencies are as important as skills in using specialized language and new technologies. Preferred are graduates who are fluent in two foreign languages (English and German) and who have extensive general knowledge.